(untitled) (Journal of Organizational Psychology, 2017)
In a 1993 op-ed piece in the Washington Post, then-Secretary of Labor Robert Reich proposed that employees reveal their job attitudes through the pronouns they use to describe their organization, specifically suggesting that employees who describe their organization using the pronoun “we” are more engaged and committed, whereas the opposite is true for those who use the pronoun “they.” This study empirically tested Reich’s assumption by studying the relationship between employees’ pronoun use in describing their work experiences and their work intentions. The study finds qualified evidence of a relationship between pronoun use and work intentions, under specific conditions.